Design of a Selective Filter based on 2D Photonic Crystals Materials - Lallam Farah; Badaoui Hadjira; Abri Mehadji (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Two dimensional finite differences temporal domain (2D-FDTD) numerical simulations are performed in cartesian coordinate system to determine the dispersion diagrams of transverse electric (TE) of a two-dimension photonic crystal (PC) with triangular lattice. The aim of this work is to design a filter with maximum spectral response close to the frequency 1.55 μm. To achieve this frequency, selective filters PC are formed by combination of three waveguides W1K A wherein the air holes have of different normalized radii respectively r1/a=0.44, r2/a=0.288 and r3/a= 0.3292 (a: is the periodicity of the lattice with value 0.48 μm). Best response is obtained when we insert three small cylindrical cavities (with normalized radius of 0.17) between the two half-planes of photonic crystal strong lateral confinement.